Teologia e literatura no labirinto mitodológico dos contos de Jorge Luis Borges - Carvalho, Rogério Gonçalves de (2017)
This thesis was born from the research we had left in the master's thesis. At that moment we had found two points of convergence between theology and literature. The first point is the theoretical (theology and literary theory) and the second the experiential point (faith and literary aesthetics). However, we also find that both in language and literary genre, theology and literature find themselves in unbalanced relationships. In language because of the nature of theology, which is explanatory, and the nature of literature, which is experiential. In the literary genre because these languages change their relations depending on the type of literary work. Our suspicion about myth is a point of convergence or a more “balanced” departure from the old relations of theology and literature to its mythic-symbolic nature. Thus we find Gilbert Durand's “mythodology” as a reasonable “myth-hermeneutic” to account for the myth as a starting point. If we can not have a balanced relationship at the end of the line, at a point or points of convergence, perhaps we can have a more balanced relationship at a starting point, at the “genetic” beginning of theology and literature. Mythodology, a hermeneutical task divided into two phases, a “mithanálisys” and a “mithocriticism”, was carried out in one of the best representatives of Latin American literature and model of writer under the aegis of the fantastic story, specifically of wonderful realism: Jorge Luis Borges. We chose the short stories from the works Fictions and The Aleph. In these tales we discover that the guiding myth is “Hermesian”, of synthetic imagination. We also note that his “myths” are closely related to the metaphors that Borges chose as archetypal images that permeate all his tales